Comparison of nanofluid wetting characteristics in untreated and superhydrophilic microgrooved heat pipes. (June 2021) - Zhang, Yunpeng; Liu, Bin; Jia, Xiao; Li, Shikun; Zhou, Jingzhi; Huai, Xiulan
Abstract: The thermal performance of the microgrooved heat pipes is mainly restricted by the wick capillary limit. The construction of micro-nano structures and using nanofluids are effective ways to improve the microgroove wetting characteristic and heat transfer ability. Based on the accommodation theory, a model for nanofluid wetting characteristics in the microgrooved heat pipe was presented in this paper. The axial wetting ability of SiO2 nanofluid in untreated rectangular microgrooves (RMs) and rectangular microgrooves with superhydrophilic nano-textured surfaces (RMSNSs) were compared. The results indicate that the total wetting length ( L t ) of SiO2 nanofluids in RMSNSs was remarkably longer than that in RMs. For RMs, the wetting length in the corner flow region ( L c ) could nearly be ignored. However, L c of RMSNSs increased significantly being about 35% of L t . When the nanoparticle size rose from 15 to 50 nm, L t of RMSNSs increased by about 13% but that of RMs decreased slightly. When the heat flux increased from 0 to 120 kW/m 2, L t of RMSNSs and RMs dropped by about 72.6% and 69.5% respectively due to the liquid evaporation. Also, the microgroove depth and width had remarkable effects on the wetting length and the optimal depth to width ratio was about 2:1. HIGHLIGHTS: The wetting length of nanofluid in RMSNSs is remarkably longer than that in RMs. The increase of nanoparticle size and decrease of volume fraction improve the wettability of the nanofluid in RMSNSs. The wetting length becomes shorter under a higher heat flux because of the additional flow resistance induced by evaporation. The microgroove depth and width play significant effects on wetting ability and the optimum ratio is about 2:1.